PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS YANG DI MEDIASI PERILAKU PEMBELIAN DALAM MEMILIH JASA TRANSPORTASI UDARA LION AIR RUTE BANJARMASIN-JAKARTA - suryani, Nelly; Rahmawati , Emy; Utomo, Setio (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this study to examine the effect of service quality on loyalty mediated buying behavior in choosing Lion Air airport transportation services Banjarmasin-Jakarta route. Research approach using quantitative approach, type of causal design research, population in this research is all of air transportation service of Lion Air Banjarmasin-Jakarta route, data collected by spread questioner to 120 respondents. The analysis used included validity test, reliability test, classical assumption test, regression analysis, path analysis (analysis path), t test, and coefficient of determination. The result of this study proves that the quality of service (X) has a significant effect on the loyalty (Y), the influence of 9,865%, the quality of service significantly influence the buying behavior (M), the effect of 8.527%, based on path analysis obtained direct influence of the variable of service quality X) to the variable of service user loyalty (Y) of 0, 635, regression coefficient indirect effect variable Quality of service (X) to variable service user loyalty (Y) through variable purchase behavior (M) is 0.617X0.063 = 0.038, the direct influence is greater than the indirect influence of the Purchase behavior variable can not moderate the influence of service quality to customer loyalty.